Olivopontocerebellar atrophy of neonatal onset and disialotransferrin developmental deficiency syndrome. Issue 9 (September 1991) - Horslen, S P; Clayton, P T; Harding, B N; Hall, N A; Keir, G; Winchester, B
Abstract : Two brothers presented with olivopontocerebellar atrophy of neonatal onset. The clinical features (failure to thrive, hypotonia, liver disease, effusions, and visual inattention) were similar to those of the four cases already reported, as were the necropsy findings of olivopontocerebellar atrophy, hepatic steatosis and fibrosis, and microcystic renal changes. The clinical similarities between this and the disialotransferrin developmental deficiency syndrome were noted. The characteristic abnormality of serum transferrin found in the latter syndrome was also found in the two cases reported here. We suggest that both syndromes are caused by the same, or related, defects in glycoprotein metabolism.